STRATEGI KOMUNIKASI ORGANISASI HUMAS DALAM MENYELESAIKAN KONFLIK ANTAR UMAT BERAGAMA (Studi Pada Kantor Bupati Aceh Singkil) - Nur Janah (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
Abstrak: The purpose of this study was to describe or describe strategies for organizational communicationPublic Relations, PR organizational effectiveness of communication strategies, as well as factorssupporting and inhibiting komunikas oganisasi PR strategy in resolving religious conflicts in Aceh Singkil.Methodology This study is a qualitative research with a description of the search, analyze andmake interpretation of the data found through documents, interviews and observations. The collecteddata were examined its validity through the validity of the data in the form of trust. Data analysistechnique is to reduce, present, and make conclusion of the study.Results of the study is that organizational communication strategies that do PR office of BupatiAceh Singkil in resolving religious conflicts is doing horizontal communication flows between the membersof the organization / employees who are in the same hierarchical level. While communicationstrategies do PR office Bupati Aceh Singkil in resolving conflicts among religious adherents is a communicationstrategy through conciliation, the communication strategy through negotiation or consultationand communication strategies through mediation. While the effectiveness of the communication strategyof the organization that conducted the Public Relations office of the Regent of Aceh Singkil in resolvingconflicts between religious communities is a formal communication such as communication by usingcommunication technology as a communication channel, as well as informal communication channelssuch as talking directly to obtain information or provide information. Implementation of these activitiesfosters a desire for greater participation in leaders and employees of the organization. With severalcontributing factors: cooperation between organizations, means of communication and transport facilities,as well as some of the inhibiting factors: lack of discipline, lack of quality skills, the location, thedifferent levels of education, and language differences.